Penggunaan Media Sosial Sebagai Peningkatan Brand Awareness pada Tim Digital Marketing PT. Otak Kanan - Rusdi Hidayat Nugroho; Kinanti Sekar Kirana (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Social media has become a trend that is well known in various circles of society in various age groups, so it is very easy to take advantage of the popularity of social media for marketing, therefore the aim of this research is to find out, observe and provide solutions using methods by observing media use practices. social by team Digital Marketinng PT. Otak Kanan. As well as using qualitative methods by using actual data and by making in-depth observations, and using literature which also has the same preparation as other research methods. By using social media & the Digital Marketing Team to carry out marketing activities, a company can promote its brand and company image with creative, relevant and interesting content to show to the general public, so as to increase Brand Awareness to the public.